High pressure study of sodium trihydride - Marqueño, Tomas; Kuzovnikov, Mikhail A.; Osmond, Israel; Dalladay-Simpson, Phillip; Hermann, Andreas; Howie, Ross T.; Peña-Alvarez, Miriam (Frontiers in Chemistry, 2024)
The reactivity between NaH and H 2 has been investigated through a series of high-temperature experiments up to pressures of 78 GPa in diamond anvil cells combined with first principles calculations. Powder X-ray diffraction measurements show that heating NaH in an excess of H 2 to temperatures around 2000 K above 27 GPa yields sodium trihydride (NaH 3 ), which adopts an orthorhombic structure (space group Cmcm). Raman spectroscopy measurements indicate that NaH 3 hosts quasi-molecular hydrogen (H δ−2 ) within a NaH lattice, with The H δ− 2 stretching mode downshifted compared to pure H 2 (∆ν ∼120 cm −1 at 50 GPa). NaH 3 is stable under room temperature compression to at least 78 GPa, and exhibits remarkable P-T stability, decomposing at pressures below 8 GPa. Contrary to previous experimental and theoretical studies, heating NaH (or NaH 3 ) in excess H 2 between 27 and 75 GPa does not promote further hydrogenation to form sodium polyhydrides other than NaH 3 .